2017
DOI: 10.18632/oncotarget.17223
|View full text |Cite
|
Sign up to set email alerts
|

Global scientific trends on exosome research during 2007-2016: a bibliometric analysis

Abstract: BackgroundExosomes are small vesicles of endosomal origin, and they can be used for the diagnosis and the treatment. However, limited data were for the evaluation of the trend of exosome researches. This study aims to investigate the trend of exosome researches and compare the contribution of research from different regions, organizations and authors.MethodsExosome related publications from 2007 to 2016 were retrieved from the Web of Science database. Excel, GraphPad Prism 5 and VOSviewer software were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…In another study, Hindex of the Iranian scientific productions on orthopedics was 17 (7). Furthermore, the H-Index of research papers on cardiovascular disease, cancer, diabetes, chronic respiratory disease and exosome research is reported to be 77, 150, 87, 36 and 74, respectively (8,9). Overall, the documents had received 7262 citations, 6.2% of which were self-citation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Hindex of the Iranian scientific productions on orthopedics was 17 (7). Furthermore, the H-Index of research papers on cardiovascular disease, cancer, diabetes, chronic respiratory disease and exosome research is reported to be 77, 150, 87, 36 and 74, respectively (8,9). Overall, the documents had received 7262 citations, 6.2% of which were self-citation.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric techniques can be used to perform statistical and quantitative analysis of publications and offer a convenient way to visibly measure researchers' efforts in the investigation of a specific field [11]. Such analyses can characterize the development in a certain field and have contributed substantially to informing policy making, clinical guidelines, and research trends [12]. Impact factors (IF) were taken from those published by the WOS in 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The top 10 most cited papers. The author keywords of a research document provide the information that the authors consider important to be highlighted and a statistical analysis of them helps to identify the research hotspot information of a particular field [40]. The most frequently used keywords, which were mentioned by at least 18 documents, are listed in Figure 2.…”
Section: Most Frequently Cited Papersmentioning
confidence: 99%